Cartoon Film As A Medium of Moral Education for Early Children - Hamdanah Hamdanah; Surawan Surawan; Noor Fahmi (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
Films always have a special message, both in characterization and portrayal in acting, of course, have their own value in making conclusions from the point of view of each audience. Therefore, the purpose of this study is to find out moral education, especially the material contained in Alif and Alya cartoons. This research uses the library research method which aims to explore information through previous research and utilize literature both manually and online with primary data sources, namely video recordings of Alif and Alya cartoons and various other sources as secondary data. The data collection techniques used are indirect observation methods and documentary methods, while the data analysis techniques used are semiotic approaches by playing Alif and Alya cartoon videos. The results showed that in the cartoons of Alif and Alya in episode 2 "Ayo Berpuasa" and episode 3 "Sharing Victory" there are moral education materials in the form of following the teachings of the Prophet of Allah, patience, repentance, honesty, respect for parents, gratitude, sincerity, and mutual forgiveness and in the cartoons Alif and Alya there are also despicable morals in the form of showing off (riya) and discrimination